Eutrophication: A Multifaceted Examination of Processes, Impacts, and Remedial Approaches in Contemporary Aquatic Environments - KUMAR MANOJ; PRANAY PUNJ PANKAJ (The Bioscan, 2024)
Eutrophication, propelled by excessive anthropogenic activities, has become a pressing global concern. This phenomenon entails the enrichment of water ecosystems with nutrients, predominantly nitrogen and phosphorous, fostering excessive biomass production and culminating in the development of hypoxic and anoxic conditions within aquatic habitats. While historically confined to freshwater bodies like ponds, lakes, and rivers, eutrophication has progressively encroached upon marine environments, notably coastal ecosystems, affecting freshwater and saline realms globally. This paper delves into the contemporary landscape of eutrophication, elucidating its principal drivers, deleterious repercussions, and prospective mitigation strategies. The study underscores the imperative of adopting comprehensive measures to curb eutrophication at a global scale for the sustainable management of water resources.